Conflict, taxation, and development - Anna D'Souza; Zachariah Cherian Mampilly (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
The impact of conflict on taxation and development has long been debated. Most studies suggest that conflict will have a depressive effect on state tax collection, negatively impacting economic growth and development. After reviewing the existing literature, we argue for an approach that recognizes conflict's nuanced effects on taxation. We show how violence can trigger the emergence of new taxation authorities, specifically non-state armed groups, including both criminal organizations and insurgent groups. These non-state groups may introduce new forms of taxation or expand existing tax practices resulting in an overall increase in taxation when combined with state taxation revenues. For ordinary civilians, the effect may be an overall increase in the amount and types of taxes they pay even as state services decrease.
Keywords: 330; conflict; taxation; development; non-state armed groups